Biology of the aquatic isolates of Sclerotium rolfsii - S. CHAURASIA; M. LAL, R. CHAND*, R. VERMA, S.K. SINGH (Indian Phytopathology, 2003)
Sclerotium rolfsii Sac. is a soil borne facultative parasite and induces root rot over 500 species of plants. It is a terrestrial fungus, although, some isolates are adapted to aquatic environment. The biology and ecology of terrestrial isolates of S. rolfsii are well studied. The present investigations were undertaken to evaluate aquatic pathogenic isolates of S. rolfsii.